Chemical and morphological mechanisms of synthesizing rectangular cesium tungsten bronze nanosheets with broadened visible-light absorption and strong photoresponse property. (September 2020) - Liu, Guanghui; Xu, Ju; Li, Ruixing
Abstract: Recently, nano-cesium tungsten bronze (Cs x WO3 ) is found to be a new candidate for the application in solar filter due to its high visible transmittance and excellent near-infrared shielding ability. However, a typical two-dimensional (2D) Cs x WO3 has not been reported since 2D nanomaterials have attracted great attention due to their fascinating properties, e.g., graphene. Herein, a novel synthesis system and related mechanisms are tried to develop for synthesizing 2D Cs x WO3 via hydrothermal method, which an original inspiration derived from the morphology control of sulfides. The results indicate that morphology modifier represents a new strategy in which thiourea and oleylamine interact synergistically rather than independently to synthesize 2D Cs0.3 WO3 . The more regular and larger the rectangular nanosheet, the broader and stronger the light absorption, the rectangular Cs0.3 WO3 nanosheets with the maximum size are synthesized from thiourea, oleylamine and HCl concentrations of 4, 0.061 and 320 mmol/L, respectively, and exhibit a broad and strong absorption spectrum. The above nanosheet shows excellent instantaneous photo-thermal conversion property resulting in an obvious temperature increases from 20 °C to 88.5 °C when it was irradiated by 50 W halogen lamp for 10 s. Finally, both chemical reaction and morphological evolution in the synthesis processes are revealed. Graphical abstract: Unlabelled Image Highlights: Thiourea and oleylamine synergistically modify two-dimensional Cs0.3 WO3 morphology. The more regular and larger the nanosheet, the broader and stronger light absorption. Thiourea, oleylamine and HCl are 4, 0.061 and 320 mmol/L, getting the maximum size. The mechanism of chemical and morphological for two-dimensional Cs0.3 WO3 is revealed. The temperature of the largest rectangular-sheets reaches 88.5 °C after irradiation.